Reversible total atrioventricular block in a very high-risk non-ST-elevation myocardial infarction (NSTEMI) during conservative treatment in a limited resource setting: a case report - Susanti Mareta Anggraeni; Ruth Grace Aurora (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Total atrioventricular (AV) block is the most common type of conduction disorder found in acute coronary syndrome (ACS), which requires timely recognition and treatment. This case report aimed to present conservative medical treatment for managing total AV block (TAVB) in a very high-risk non-ST-elevation myocardial infarction (NSTEMI) in a rural area. We reported a patient with TAVB in a very high-risk NSTEMI. The patient was hemodynamically unstable and needed immediate percutaneous coronary intervention (PCI). Due to limited facilities and difficult access to immediate PCI, the patient was treated conservatively with the NSTEMI protocol. Epinephrine, as a β-adrenergic agonist, was administered to improve hemodynamic status. During conservative treatment, TAVB was converted into the first-degree AV block on the third day of intensive care. In a setting where revascularization strategies and pacemaker implantation are not feasible, administration of antithrombotic agents and β-adrenergic agonists can be considered to manage TAVB with NSTEMI with close monitoring.